Relationship Betweent Anxiety With Quality of Life For Hypertension In UPTD Puskesmas Demangan Kota Madiun - Adelia Kusuma Prasetiyo Putri; Riska Ratnawati; Avicena Sakufa Marsanti (Health Science UDINUS, 2024)
Hypertension is an increase in systolic blood pressure from normal to 140 mmHg and diastolic pressure more than 90 mmHg. This hypertension has an impact on the low quality of life, especially in the domain of physical function. Based on Basic Health Research (Riskesdas) data for 2018, Indonesia has experienced a quite drastic increase in prevalence. From 25.8% in 2013 it has now increased to 34.1%. Depression, anxiety, and stress can also affect the quality of life of people with hypertension. This study aims to determine the relationship between anxiety and the quality of life of hypertensive patients. This study used a cross sectional approach. The total population in this study of 137 and 58 samples in the study. Samples were selected based on criteria, namely those who were recorded as sufferers in the area, sample selection using quota sampling technique. Data collection was carried out using dass-42 and whoqol scale questionnaires. Data analysis in this study was bivariate using the Kendall Tau test. The results of this study the results showed that the value (p value= 0.002 : Cc=-0.389). It can be concluded that there is a relationship between anxiety and the quality of life of hypertension sufferers